FOOD OF THE CAT-FISH, TACHYSURUS THALASSINUS (RUPPELL) - Mojumder, P (Indian Journal of Fisheries, 2011)
The food habits of the cat-fish, Tachysurus thalassinus, v/eit studied for a period of three years from April 1964 to March 1967, based mainly on specimens from the fishing areas oif Waltair, and also some from further north in the Bay of Bengal. From the pooled data of all zones it is observed that 67% of the food consists of crabs, prawns, Squilla spp., and crustacean remains, 22% of teleosts and 4% of molluscs. The-fluctuations in the intensity of feeding (points) and the volume of stomach contents (ml) generally showed similar trends both in the small (less than 36 cm total length) and large (more than 36 cm total length) cat-fish; A rough correlation between the stomach contents and the availability of food items in the environment is observed